2012
DOI: 10.1371/journal.ppat.1002826
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Site-Specific Adaptations Conferring Increased Neural Cell Tropism during Human Enterovirus 71 Infection

Abstract: Enterovirus 71 (EV71) is one of the most virulent enteroviruses, but the specific molecular features that enhance its ability to disseminate in humans remain unknown. We analyzed the genomic features of EV71 in an immunocompromised host with disseminated disease according to the different sites of infection. Comparison of five full-length genomes sequenced directly from respiratory, gastrointestinal, nervous system, and blood specimens revealed three nucleotide changes that occurred within a five-day period: a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
99
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(106 citation statements)
references
References 73 publications
6
99
1
Order By: Relevance
“…A replacement of Glu with Lys at position 167 increased the positive electrostatic potential, which may restore their interactions between VP1 monomers, thereby stabilizing the capsid assembly. Interestingly, mutation E167G or E167A was found to be frequently associated with the VP1 L97R mutation, which conferred increased neural cell tropism during human EV71 infection (24), suggesting that residue E167 plays an central role in capsid assembly through interaction with residues L97 and R250. For mutant K274A, both mutations I111L and A224V could rescue the lethal phenotype of the K274A mutation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A replacement of Glu with Lys at position 167 increased the positive electrostatic potential, which may restore their interactions between VP1 monomers, thereby stabilizing the capsid assembly. Interestingly, mutation E167G or E167A was found to be frequently associated with the VP1 L97R mutation, which conferred increased neural cell tropism during human EV71 infection (24), suggesting that residue E167 plays an central role in capsid assembly through interaction with residues L97 and R250. For mutant K274A, both mutations I111L and A224V could rescue the lethal phenotype of the K274A mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Several key residues in the VP1 protein involved in pathogenesis have been identified. A nonconservative amino acid change in VP1 located within the BC loop (L97R) contributes to dissemination and neurotropism in immunocompromised patients (24). The residue at position 145 of VP1 (VP1-145) controls virus tropism by changing the accessibility of the positively charged lysine side chain of VP1-244 to the negatively charged N terminus of PSGL-1 on leukocytes (25) and has been implicated as one of the possible determinants of virulence in humans (26,27).…”
mentioning
confidence: 99%
“…In a complex environment, the ability to generate a quasispecies may allow virus populations to respond and adapt fast (43)(44)(45)(46). Fidelity variants with wild-type-like replication kinetics are valuable tools to understand the roles of genetic diversity and mutation frequency in viral fitness and to evaluate the antiviral treatments (47).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of whole genome sequences has been used to reveal epidemiologic and evolutionary dynamics of EVs through time and space [1,39,51]. Studies of EVs suggested that sequence variations in the UTRs, the VP1 region and the 3D polymerase could affect virus infection and replication capability in vitro and in vivo [103,104].…”
Section: Molecular Diversity and Evolution Of Enterovirusesmentioning
confidence: 99%